Formas de mensurar a sustentabilidade: um estudo sobre os novos indicadores - Souza, Adriana Silva de (2011)
The reflection on the theme development, along with pressure from society in nature, led the growth in awareness of the environmental problems caused by incompatible standards of living through the process of regeneration of the environment. With that sustainable development has become the main choice for today's socioeconomic development. The finding of fact made researchers were in search of a development model that can guarantee the quality of life of present generations without compromising the ability of future generations to survive and develop. Several tools have been developed in recent years with the aim of measuring the sustainability of economic and social systems. In an attempt to improve knowledge of sustainability indicators in this study evaluated three of the tools most widely used and recognized in the context of sustainability: the Ecological Footprint, the Dashboard of Sustainability, and the Barometer of Sustainability. The three tools were evaluated in order to identify the main elements of these indicators and their theoretical basis. The ultimate goal is to write a comparative analysis and improve understanding of sustainability indicators mentioned so that you can use these tools more clearly and consciously